2022
DOI: 10.1098/rsob.220261
|View full text |Cite
|
Sign up to set email alerts
|

The role of α-sheet structure in amyloidogenesis: characterization and implications

Abstract: Amyloid diseases are linked to protein misfolding whereby the amyloidogenic protein undergoes a conformational change, aggregates and eventually forms amyloid fibrils. While the amyloid fibrils and plaques are hallmarks of these diseases, they typically form late in the disease process and do not correlate with disease. Instead, there is growing evidence that smaller, soluble toxic oligomers form prior and appear to be early triggers of the molecular pathology underlying these diseases. Nearly 20 years ago, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…21 In our case, we also demonstrated that PSMa3 maintains a-helical conformation up to several days of incubation at 37 1C, wherein a-helical-designed peptides were shown before to suppress amyloid aggregation with high efficiency, including both bacterial and mammalian peptides and proteins. [64][65][66][67] This is probably determined by the fact that the formation of intermediate cross-a-sheet-like structures is a universally adopted amyloidogenic motif during the amyloid selfassembly process, which has been shown to be associated with high toxicity and demonstrated before for the different pathogenic amyloids, such as Ab, a-syn, transferrin, amylin, and others. 64,[68][69][70][71] In particular, these kinds of transient oligomer species, composed primarily of a-sheets, were also described before for human insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In our case, we also demonstrated that PSMa3 maintains a-helical conformation up to several days of incubation at 37 1C, wherein a-helical-designed peptides were shown before to suppress amyloid aggregation with high efficiency, including both bacterial and mammalian peptides and proteins. [64][65][66][67] This is probably determined by the fact that the formation of intermediate cross-a-sheet-like structures is a universally adopted amyloidogenic motif during the amyloid selfassembly process, which has been shown to be associated with high toxicity and demonstrated before for the different pathogenic amyloids, such as Ab, a-syn, transferrin, amylin, and others. 64,[68][69][70][71] In particular, these kinds of transient oligomer species, composed primarily of a-sheets, were also described before for human insulin.…”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66][67] This is probably determined by the fact that the formation of intermediate cross-a-sheet-like structures is a universally adopted amyloidogenic motif during the amyloid selfassembly process, which has been shown to be associated with high toxicity and demonstrated before for the different pathogenic amyloids, such as Ab, a-syn, transferrin, amylin, and others. 64,[68][69][70][71] In particular, these kinds of transient oligomer species, composed primarily of a-sheets, were also described before for human insulin. 72 It was also recently demonstrated that the mechanism of inhibition of insulin fibrillation by short ahelical peptides is based on hydrogen bond formation with amino acid residues in both insulin chains that interfere with the insulin conformational transition from a-helix to b-sheet.…”
Section: Discussionmentioning
confidence: 99%
“…The proposal had previously been made (recently [ 23 , 24 , 25 ]) that AD is caused by a toxic protein conformation called α-sheet, a protein conformation discovered by Pauling and Corey [ 26 , 27 ] before they discovered the well-known β-sheet. Molecular dynamics simulation has shown that α-sheets and β-sheets can interconvert [ 25 , 28 , 29 ], with interconversion stimulated by side-chain hydrophilicity [ 25 ].…”
Section: Introduction: Previous Data and Our Best-fit Modelmentioning
confidence: 99%
“…The proposal had previously been made (recently [ 23 , 24 , 25 ]) that AD is caused by a toxic protein conformation called α-sheet, a protein conformation discovered by Pauling and Corey [ 26 , 27 ] before they discovered the well-known β-sheet. Molecular dynamics simulation has shown that α-sheets and β-sheets can interconvert [ 25 , 28 , 29 ], with interconversion stimulated by side-chain hydrophilicity [ 25 ]. The α-sheet-as-disease-causing-agent proposal is dramatically supported by the observation that the toxic form of in vitro-assembled AD amyloid proteins (cleaved Aβ protein, 40–42 amino acids long; review [ 28 , 29 ]) have two characteristics of α-sheets: (1) circular dichroism near zero and (2) an appropriate NMR signature [ 23 , 24 , 25 ].…”
Section: Introduction: Previous Data and Our Best-fit Modelmentioning
confidence: 99%
“…α-Sheet is defined by the alignment of the amide groups on one side of the backbone and the carbonyl groups on the other (Daggett, 2006). We designed nontoxic, stable α-sheet peptides complementary to the presumed α-sheet structure in the toxic oligomers (Bleem et al, 2017;Bleem et al, 2023;Daggett, 2006;Hopping et al, 2014;Kellock et al, 2016;Maris et al, 2018;Prosswimmer & Daggett, 2022;Shea et al, 2019). We reasoned that these α-sheet peptides would neutralize toxicity and inhibit fibril formation by specifically binding to toxic oligomers.…”
Section: Introductionmentioning
confidence: 99%